2015
DOI: 10.1155/2015/417565
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Carrot Expressing Fusion Protein ComprisingM. tuberculosisAntigens Induces Immune Response in Mice

Abstract: Tuberculosis remains one of the major infectious diseases, which continues to pose a major global health problem. Transgenic plants may serve as bioreactors to produce heterologous proteins including antibodies, antigens, and hormones. In the present study, a genetic construct has been designed that comprises the Mycobacterium tuberculosis genes cfp10, esat6 and dIFN gene, which encode deltaferon, a recombinant analog of the human γ-interferon designed for expression in plant tissues. This construct was transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Till date, no study has been reported regarding expression of any vaccine antigen in broccoli. The expression of ESAT‐6 protein obtained in the present study is fairly high compared with previously expressed ESAT‐6 antigen in edible plants using nuclear transformation.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Till date, no study has been reported regarding expression of any vaccine antigen in broccoli. The expression of ESAT‐6 protein obtained in the present study is fairly high compared with previously expressed ESAT‐6 antigen in edible plants using nuclear transformation.…”
Section: Discussionmentioning
confidence: 55%
“…Results show that the orally delivered recombinant ESAT‐6 expressed in broccoli plant and purified ESAT‐6 derived from transgenic broccoli have the potential to induce humoral response. Previous studies have also shown that ESAT‐6 from M. tuberculosis had the potential to elicit the cellular and humoral responses in mice . Results of oral immunization using the raw plant biomass are of special interest because it is the most advantageous immunization strategy in terms of cost and easy application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that corresponding protein antigens may be successfully expressed following DNA vaccine administration, and these protein antigens are capable of simulating a natural infection and producing a more comprehensive immune response (8,9). The antigen-specific cellular and humoral immune responses must be detected following administration of a DNA vaccine directed against a pathogenic microorganism or malignant tumor, in order to evaluate the immune effects of the DNA vaccine.…”
Section: Introductionmentioning
confidence: 99%